2001
DOI: 10.1111/0022-1082.00333
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Portfolio Choice for Long‐Horizon Investors with Nontradable Labor Income

Abstract: This paper examines how risky labor income and retirement affect optimal portfolio choice. With idiosyncratic labor income risk, the optimal allocation to stocks is unambiguously larger for employed investors than for retired investors, consistent with the typical recommendations of investment advisors. Increasing idiosyncratic labor income risk raises investors' willingness to save and reduces their stock portfolio allocation towards the level of retired investors. Positive correlation between labor income an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
350
3
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 654 publications
(363 citation statements)
references
References 55 publications
9
350
3
1
Order By: Relevance
“…Viceira (2001) showed that high indiosyncratic labor income risk and positive correlation between stock returns and labor income can mean that the stockholdings of the young should be lower than those of retired investors. His calculations also show that the optimal portfolio can depend a lot on assumptions that are made about preferences and stochastic properties of variables, and under some assumptions the optimal portfolio may look quite extreme.…”
Section: Defining Life-cycle Fundsmentioning
confidence: 99%
“…Viceira (2001) showed that high indiosyncratic labor income risk and positive correlation between stock returns and labor income can mean that the stockholdings of the young should be lower than those of retired investors. His calculations also show that the optimal portfolio can depend a lot on assumptions that are made about preferences and stochastic properties of variables, and under some assumptions the optimal portfolio may look quite extreme.…”
Section: Defining Life-cycle Fundsmentioning
confidence: 99%
“…52 Figure 8 illustrates how Σ 11 varies with ρ 2 and σ 2 /σ 1 . 53 It clearly shows that given the persistence and volatility coefficients of y 1,t , the estimation risk increases with the persistence and volatility of y 2,t (i.e., the less ρ 2 and the higher σ 2 /σ 1 ).…”
Section: Comparison With Incomplete Information About Individual Labomentioning
confidence: 92%
“…They found that labor income is the most important source of wealth and labor income risk is weakly positively correlated with equity returns. Viceira (2001) examined the effects of labor income risk on optimal consumption and portfolio choice for both employed and retired investors. Campbell (2006) outlined the field of household finance and argued that some house- 1 Here we label model uncertainty or state uncertainty "induced uncertainty" because it is induced by the interactions of the preference for robustness or information-processing constraints with fundamental uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in setting the default portfolio, one can take into account other characteristics of members besides age-such as the nature of human capital, the income level, the flexibility of retirement choices implied by the flexibility of the labour market for elderly and owner-occupied housing and its financing. To illustrate, agents with particularly risky human capital that is strongly correlated with financial-market risks should invest less in risk-bearing assets (see Viceira 2001). The same holds true for workers that are liquidity constrained, face substantial idiosyncratic human-capital risk, exhibit habit formation, and do not exhibit much flexibility in their retirement choices and thus cannot use the speed and timing of retirement to absorb risks (see Bodie et al 1992;and Gollier 2005).…”
Section: Improve Risk Sharing Between Cohortsmentioning
confidence: 99%